2022
DOI: 10.1093/infdis/jiac337
|View full text |Cite
|
Sign up to set email alerts
|

Celebrating 25 Years of Varicella Vaccination Coverage for Children and Adolescents in the United States: A Success Story

Abstract: Tracking vaccination coverage is a critical component of monitoring a vaccine program. Three different surveillance systems were used to examine trends in varicella vaccination coverage during the United States vaccination program: National Immunization Survey–Child, National Immunization Survey–Teen, and immunization information systems (IISs). The relationship of these trends to school requirements and disease decline was also examined. Among children aged 19–35 months, ≥1 dose of varicella vaccine increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A UVV program in the United States resulted in net societal savings of $23.4 billion in its first 25 years [ 47 ]. Furthermore, the introduction of a UVV program in the United States was associated with 97% reduction in varicella cases [ 5 ] with an estimated $259 million reduction in antibiotic and antiviral prescription costs per year [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A UVV program in the United States resulted in net societal savings of $23.4 billion in its first 25 years [ 47 ]. Furthermore, the introduction of a UVV program in the United States was associated with 97% reduction in varicella cases [ 5 ] with an estimated $259 million reduction in antibiotic and antiviral prescription costs per year [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization recommends universal vaccination as one of the main preventive interventions where varicella is a public health problem, yet only 39 countries have universal varicella vaccination (UVV) programs [ 2 ]. Varicella vaccination has been part of the recommended pediatric immunization schedule in the United States for >25 years, which has resulted in a substantial decrease in disease burden [ 5 ]. Within Europe, several countries have a lower varicella prevalence as a result of UVV programs [ 1 , 6 ].…”
mentioning
confidence: 99%
“…The literature has shown that a one-dose varicella vaccine is more cost-effective than a two-dose vaccine [ 28 ], but the rate of breakthrough infections with a one-dose vaccine is higher than that with a two-dose vaccine [ 29 , 30 ]. Therefore, considering multiple perspectives of evidence, it is essential to provide children with two doses of the routine varicella vaccine, and high coverage of two-dose varicella vaccination should be achieved to maximise the benefits of the varicella vaccination program [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Optimistic and Conservative Timeline scenarios, it is assumed that ramp-up to peak coverage takes place over 5 years and 15 years, respectively. This assumption is based on WHO vaccine surveillance reporting for infant and childhood vaccines introduced in public markets across country income levels within the last 20 years, including PCV3, RotaC, MCV2, and second dose of varicella (greater than 10 years to reach peak coverage) 20 , 49 .…”
Section: Methodsmentioning
confidence: 99%